Transition to the improved confinement mode in torsatron U-3M in range of rare collision frequencies - Pashnev, V.K.; Sorokovoy, E.L.; Berezhnyj, V.L.; Burchenko, P.Ya.; Volkov, E.D.; Krasnyj, V.V.; Lozin, A.V.; Mironov, Yu.K.; Petrushenya, A.A.; Pinos, I.B.; Skibenko, A.I.; Slavnyj, A.S.; et al. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Transition to the mode of improved plasma confinement in U-3M facility earlier was discussed in works [1-3]. In these studies discussed the various processes in the confinement volume and in the peripheral plasma that accompany the transition process. Study of plasma confinement and process of transition into the mode of improved confinement just at rare collisions between plasma particles is very important because future fusion reactor based on a toroidal magnetic trap will operate under plasma parameters with rare collision frequencies (“banana” mode). The peculiarity of experiments on torsatron U-3M is that they are conducted at small density ne ≤ 2×10^12 cm^-3 and, thereby, the frequency of collisions in the confinement area is in the "banana" mode [4]. And herewith, time of collisions is essentially smaller (up to several orders for electrons and up to the order for ions) than the lifetime of plasma particles. It ensures maxwellization of distribution function and possibility to compare the obtained results with data from other experiments. The objective of this work is to study the main regularity of transition into the mode of improved confinement. Also it is interesting to compare the results with data from other facilities.